THE INFLUENCE OF TOPICAL HYPOTENSIVE DRUGS ON THE REDUCTION OF THE DECREASE OF VISUAL FIELD SENSITIVITY DUE TO OPTIC NERVE HEAD DRUSEN – CASE REPORT: CASE REPORT - Radenkovic, Marija (Medicinski časopis, 2022)
ABSTRACT Optic nerve head drusen are congenital anomaly of the optic nerve, a form of calcium degeneration of axons of the optic nerve head. Initially asymptomatic, drusen may be one of the causes of progressive optic neuropathy. Clinicaly presented as acellular, hyaline deposits of globular appearance in prelaminar segment of the optic nerve head. Occurence due to: altered axonal transport, small diameter of scleral channel, compression and ischemia. Frequent complications are progressive visual field defects, ischemic optic neuropathy, central retinal artery or vein occlusion, peripapilar neovascularization. Diagnostic tools: ophthalmoscopy, angiography, computerized perimetry, B-scan ultrasonography, CT, OCT, HRT, GDx, electrophysiological testing. Treatment is medicamentous, laser, surgery. Most of the pilot study confirms benefit of topical hypotensive drugs even when drusen are not associated with glaucoma. Decrease of intraocular pressure reduces compression of the optic nerve axons and improves reperfusion. This paper presents a young patient with bilateral optic nerve head drusen, progressive scotoma and administered topical hypotensive medication. After six months, scotoma and loss of sensitivity were reduced. The effect of neuroprotective drugs is researched to reduce potential morbidity. Key words: optic nerve head (ONH) drusen, visual field, scotoma, hypotensive drug